1999
DOI: 10.1002/(sici)1099-1166(199907)14:7<526::aid-gps965>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of three clinical criteria for dementia with Lewy bodies in an autopsy‐verified sample

Abstract: This study demonstrated that additional improvements in the established criteria for DLBD are needed. Our empirically derived criteria enhanced the distinction of DLBD from AD while allowing the clinician the choice of maximizing sensitivity with acceptable specificity, and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 0 publications
0
31
0
3
Order By: Relevance
“…Minoshima et al found that the presence of occipital hypometabolism distinguished DLB from AD with 90% sensitivity and 80% specificity in a study using a postmortem diagnostic validation (41). Minoshima et al found that the sensitivity in discriminating DLB and AD using 18 F-FDG PET was greater than that with clinical diagnostic criteria applied retrospectively to the data from medical charts (41,46). The sensitivity was also greater than a carefully designed prospective clinicopathologic correlation study (47), but direct comparison is difficult because of the different populations of patients in these studies.…”
Section: Ad Versus Dlbmentioning
confidence: 99%
“…Minoshima et al found that the presence of occipital hypometabolism distinguished DLB from AD with 90% sensitivity and 80% specificity in a study using a postmortem diagnostic validation (41). Minoshima et al found that the sensitivity in discriminating DLB and AD using 18 F-FDG PET was greater than that with clinical diagnostic criteria applied retrospectively to the data from medical charts (41,46). The sensitivity was also greater than a carefully designed prospective clinicopathologic correlation study (47), but direct comparison is difficult because of the different populations of patients in these studies.…”
Section: Ad Versus Dlbmentioning
confidence: 99%
“…Five Class II studies also showed low sensitivities (average across 5 studies = 58%, range 34 to 75%) but higher specificities (average across 5 studies = 87%, range 71 to 94%) for the diagnostic criteria of Consortium for DLB. 10,[30][31][32][33] In a prospective clinical study based on a DLB case registry with neuropathologically confirmed cases, hallucinations, depression, delusions, and delusional misidentification were all significantly higher in patients with DLB than AD. 34 However, all of these features occurred in patients with AD as well.…”
Section: Vascular Dementia (Vad)mentioning
confidence: 99%
“…The specificity of the Consensus criteria has been reported to range from 29% to 100% and the sensitivity from 22% to 90%. [6][7][8][9][10][11][12] Thus far there has only been one prospective study, 13 in which the sensitivity of the Consensus criteria for DLB was 83% and the specificity was 95%. Thus, at best, the Consensus criteria perform fairly well, particularly in specialised centres with an interest in DLB, and certainly no worse than diagnostic criteria for AD 14 15 or Parkinson's disease (PD), 16 but nevertheless at least 15% of patients will continue to be misclassified.…”
mentioning
confidence: 99%